Identification and Fine-Mapping of a Novel QTL, qMrdd2, That Confers Resistance to Maize Rough Dwarf Disease - Xu, Zhennan (Plant disease, 2022)
Maize rough dwarf disease (MRDD) is caused by a virus and seriously affects maize quality and yield worldwide. MRDD can be most effectively controlled with disease-resistant hybrids of corn. Here, MRDD-resistant (Qi319) and -susceptible (Ye478) parental inbred maize lines and their 314 recombinant inbred lines (RILs) that were derived from a cross between them were evaluated across three environments. A stable resistance QTL, qMrdd2, was identified and mapped using best linear unbiased prediction (BLUP) values to a 0.55-Mb region between the markers MK807 and MK811 on chromosome 2 (B73 RefGen_v3) and was found to explain 8.6 to 11.0% of the total phenotypic variance in MRDD resistance. We validated the effect of qMrdd2 using a chromosome segment substitution line (CSSL) that was derived from a cross between maize inbred Qi319 as the MRDD resistance donor and Ye478 as the recipient. Disease severity index of the CSSL haplotype II harboring qMrdd2 was significantly lower than that of the susceptible parent Ye478. Subsequently, we fine-mapped qMrdd2 to a 315-kb region flanked by the markers RD81 and RD87, thus testing recombinant-derived progeny using selfed backcrossed families. In this study, we identified a novel QTL for MRDD resistance by combining the RIL and CSSL populations, thus providing important genetic information that can be used for breeding MRDD-resistant varieties of maize